2000
DOI: 10.1046/j.1523-1755.2000.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein-70 repairs proximal tubule structure after renal ischemia

Abstract: These data support the hypothesis that HSP-70 interacts with cytoskeletal elements during the restoration of proximal tubule cell structure and polarity after renal ischemia. This experimental approach represents a new in vitro assay to study further the role of HSP in cellular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 11 publications
4
61
1
2
Order By: Relevance
“…In other injury models, overexpression of Hsp70 via transfection before nonlethal injury resulted in significantly faster stabilization of the cytoskeleton during a subsequent recovery period (26,29,31). Here, we could demonstrate for the first time a significant stabilization of cellular integrity in a CD model after transient transfection with Hsp70.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In other injury models, overexpression of Hsp70 via transfection before nonlethal injury resulted in significantly faster stabilization of the cytoskeleton during a subsequent recovery period (26,29,31). Here, we could demonstrate for the first time a significant stabilization of cellular integrity in a CD model after transient transfection with Hsp70.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies from our group in kidney cells and mesothelial cells provide evidence for a distinct cytoprotective role of HSP in various aspects of cytoskeletal disruption and reorganization in epithelial cells after nonlethal injury (26,29,31,32). Sziksz et al (30) reported in-vivo findings which suggest a distinct impact of the Hsp70 protein family in CD.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations